Can Urtica dioica supplementation attenuate mercury intoxication in Wistar rats? - Siouda, Wafa (Vet World, 2015)
AIM: The objective of this study was to investigate the possible protective role of nettle Urtica dioica (UD) against Hg-induced toxicity. MATERIALS AND METHODS: A total of 28 rats were equally divided into four groups: the control, the Hg (0.8 g HgCl(2)/kg in the diet), the UD (1.5 ml UD/rat by gavage), and the Hg+UD group. HgCl(2) was daily dissolved in distilled water and immediately mixed with the standard diet. A solution of daily infused fresh nettle leaves in boiling water (16 g in 25 ml) was obtained and then it was administrated by gavage. Biochemical and reproductive markers, in addition to glutathione (GSH) level (liver, kidney and testis) and the histological profiles (testis and epididymis) were evaluated after 1 month exposure. RESULTS: Compared to the control, the levels of glucose, triglycerides, urea, creatinine, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were significantly raised in the Hg group. In the latter group, the concentrations of Mg, Fe, and Ca were significantly decreased. Besides, Hg+UD group has only showed raised AST activity and reduced Mg level. Concerning the fertility markers, Hg has provoked a significant decrease in the spermatozoa’s concentration and motility and in plasma testosterone level as well. Furthermore, hepatic, renal and testicular GSH concentrations have declined significantly in the Hg treated rat compared to the control. A remarkable enhancement of the GSH level was observed in all organs of the UD group. The histological examinations of the Hg group have revealed marked testicular degeneration of the most seminiferous tubules, and showed few sperms in the lumen of epididymis ducts. However, the Hg+UD rats have demonstrated an improved histological structure with the presence of important numbers of sperms in the lumen. In addition, a clear stabilization of organized seminiferous tubules and an increased sperms’ numbers were noted in the UD supplemented rats. CONCLUSION: Nettle leaves have not only played a clear protective role during Hg intoxication, but it also enhanced hepatic, renal and testicular GSH level of Wistar rats.